The Effect of Geometric Parameters on the Performance of Solar Chimney: A Numerical and Experimental Study - Lahcene, A.; Benazza, A. Y.; Benguediab, M. (Engineering, Technology & Applied Science Research, 2020)
A numerical and experimental study of the geometric parameters of the solar chimney on the aerodynamic and thermal behavior of the air flow is presented in this paper. Several configurations were proposed in order to optimize the most efficient geometric one. Mass conservation, continuity, and energy equations are solved by the finite volume method. The increase in the radius of the collector and the inclination angle of the roof of the collector contributes favorably to the flow velocity to reach its maximum below the level of the tower, whereas it is inversely proportional to the height of the collector (space: ground-roof). This hangs up the height and the opening of the chimney generates a significant relaxation between the glue and the exit, from where important velocity is recorded at the level of the glue. A good correlation between the experimental and the simulation results is observed.